2016
DOI: 10.3390/ijms17071139
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomic Analysis Reveals the Mechanism of Phelipanche aegyptiaca Seed Germination

Abstract: Phelipanche aegyptiaca is one of the most destructive root parasitic plants of Orobanchaceae. This plant has significant impacts on crop yields worldwide. Conditioned and host root stimulants, in particular, strigolactones, are needed for unique seed germination. However, no extensive study on this phenomenon has been conducted because of insufficient genomic information. Deep RNA sequencing, including de novo assembly and functional annotation was performed on P. aegyptiaca germinating seeds. The assembled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…The seed samples (1 g) were separately ground in liquid N using a mortar and pestle. The concentrations of ABA and GA were quantified using appropriate enzyme-linked immunosorbent assay kits (Chengling, Beijing, China) according to manufacturer’s instructions [ 11 ]. The ABA and GA concentrations are reported as the mean of three biological replicates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The seed samples (1 g) were separately ground in liquid N using a mortar and pestle. The concentrations of ABA and GA were quantified using appropriate enzyme-linked immunosorbent assay kits (Chengling, Beijing, China) according to manufacturer’s instructions [ 11 ]. The ABA and GA concentrations are reported as the mean of three biological replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Six plant-hormone-related genes, two SL perception-related genes, and two genes related to P450s were selected for validation of RNA-seq by qRT-PCR. PaTubulin1 was used as an internal control [ 11 , 22 ]. The qRT-PCR was conducted using SYBR GreenER™ qPCR SuperMix Universal (Invitrogen, Gaithersburg, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structure modification of artificial germination stimulants resulted in an improvement in the germination-inducing activity [173][174][175][176]. Although conditioning prior to applying artificial germination stimulants was a prerequisite for the success of a suicidal germination approach [169,171], Yao et al [177] reported that conditioning was probably not the indispensable stage of P. aegyptiaca based on the finding that the transcript level of genes relating to SL signalling was not up-regulated by the conditioning treatment.…”
Section: Suicidal Germinationmentioning
confidence: 99%